Market information to mobiles promote transparency within Senegal's value chains - Ricau, Pierre; Tossou, Hermann S.; Osseni, Senou; Bappa Se, Marc Ghislain (Technical Centre for Agricultural and Rural Cooperation, 2019)
Digital agribusiness, N'kalô, is empowering Senegal's smallholders through the provision of reliable and objective market information to their phones. Using this data, farmers are able to negotiate to achieve the best prices for their produce.